NGAWULUKU SEBAGAI IDE PENCIPTAAN DRAWING - Dicky Candra Irawan, - (2018)
Ngawulukuadalahsalahsatukearifan lokal yang ada di Indonesia, serta merupakan tahapan proses yang terdapatdalamkegiatanpertanian di tanahsunda, ngawulukuberasaldari kata wuluku yang berartiperalatanatauperkakasuntukmembajaksawahsedangkanngawulukumerupakan proses bagaimanatentangcaramenggunakanperkakastradisionaltersebutdalam proses bertanikhususnyamembajaksawah. Orang-orang tanidalamngawulukuataumembajaksawahmerekaselalubersenandungdengan kata katasepertikiya, kalen, arang, mideur, luput. Sedangkanperkakas yang digunakandalam proses ngawulukuyaituberupaSingkal. Seiringberjalannyawaktu, proses bertaniNgawulukuwarisannenekmoyangkitamulaitergerusolehperkembanganzamankarenamasyarakatmenganggapperkakas yang digunakandalam proses tersebutkurangefektifdanefisien. Sehinggalambatlaunnama-nama,bentukperkakaspertaniantradisionalserta nilai-nilai positif yang terkandung didalamnyamulaiterlupakandanpadaakhirnyaakanterjadikehilangankosa kata padabidangtersebut. Seperti yang sudahterjadipadasaatsekarang, banyakmasyarakat yang tidakmengetahuitentangbagaimanaproses ngawulukusertabentukdannamadariperkakaspertaniantradisional. Dari uraiandiatas, munculahgagasanuntukmembuatkarya drawing dengantemangawuluku. Rumusanmasalah yang terdapatdalampenciptaaniniadalahmengembangkan ide dalampembuatankaryadrawing, visualisasikaryadrawingtersebut, sertabagaimanamenganalisiskaryadarisegi visual dankonseptual. Teknik yang digunakanadalahteknikpointilis, denganeksperimen media danterdiridarilimabuahkarya. Visualisasi ide ngawulukudibuatsedemikianrupadenganmenggunakankaidahunsurdanprinsip visual, sehingga ide tersebutmenghasilkankorelasiantarabentukfisikdrawingdengankonsepngawulukuitusendiri. Penulisberharapkaryainimampumenjadiinspirasidanbermanfaatbagisiapasaja yang mengapresiasidanmembacanya.Karyadrawinginijugadiharapkantidakhanyamenjadialternatifbahanpembelajaransenirupa di sekolah-sekolahsaja, namunjugamampumenyampaikanpesan moral akanpenyadaranmasyarakattentanglingkunganhidupdanterusmemeliharakelestariandariapa yang dimilikioleh Indonesia;---Ngawuluku is one of the local wisdoms in Indonesia, and is a process stage found in agricultural activities in Sunda land, Ngawuluku comes from the word Wuluku which means equipment or tools for plowing fields while Ngawuluku is a process of how to use these traditional tools in the process farming especially plowing fields. Peasants in Ngawuluku or plowing fields they always hum with words like kiya, kalen, arang, mideur, escape. While the tools used in the Ngawuluku process are in the form of Singkal. Over time, the process of farming Ngawuluku our ancestral heritage began to erode by the times because people consider the tools used in the process less effective and efficient. So that gradually the names, forms of traditional farming tools and the positive values contained in them begin to be forgotten and eventually there will be a loss of vocabulary in that field. As has happened at the present time, many people do not know about how the Ngawuluku process and the forms and names of traditional farming tools. From the description above, came the idea to make drawing works with my ngawuluku theme. The formulation of the problem contained in this creation is to develop ideas in making drawing works, visualizing the drawing works, and how to analyze works in terms of visual and conceptual. The technique used is pointillary technique, with media experiments and consists of five works. Visualization of ngawuluku ideas is made in such a way as to use the principles and visual principles, so that the idea produces a correlation between the physical form of the drawing and the concept of my ngawuluku itself. The author hopes that this work can be an inspiration and useful for anyone who appreciates and reads it. This drawing work is also expected not only to be an alternative material for learning art in schools, but also to be able to convey a moral message about community awareness about the environment and continue to preserve the sustainability of what Indonesia has.